126k views
5 votes
F(x)=x2+1 g(x)=5-1

(f+g)(x)=
Answer Choices are...
A: x2+x-4
B: x2+x+4
C: x2-x+6
D: x2+x+6
Help is Appreciated! :)

1 Answer

6 votes

Answer:Given that f ( x ) = 2 x − 3 f(x)=2x-3 f(x)=2x−3f, left parenthesis, x, right parenthesis, ... \end{aligned} (f⋅g)(x)​=f(x)⋅g(x)=(2x−3)⋅(x+1)=2x2+2x−3x−3=2x2−x−3​Define. ... Choose 1 answer: ... (Choice B) ... the new graph will pass through the two points (4, 0) and (6,-6) which only happens in Graph B. ... (c*d)(y) = (3y-4)(3-2y

Explanation:

Just google it or do the math :)

p.s I googled it .

Hoped i helped you !

User Manmohan Pal
by
5.4k points